A Comprehensive SWOT Analysis of Pangasius Production in Kailali District, Nepal - Bhatta, Dharma Dev; Pant, Khem Raj; Sapkota, Liladhar; Upadhyay, Govinda (AMC Journal (Dhangadhi), 2024)
Pangasius farming has become a vital part of Nepal's aquaculture sector, particularly in the Kailali district. This research conducts a comprehensive SWOT analysis to identify the strengths, weaknesses, opportunities, and threats associated with Pangasius production in this region. The analysis draws on quantitative and qualitative data collected from local fish farmers, highlighting the economic and environmental factors influencing the industry. The findings suggest significant potential for growth but also emphasize the need for strategic initiatives to address existing challenges and ensure sustainable development. Policy implications include increased government support, improved market structures, and development of strategic interventions to enhance sustainability and competitiveness.